PENINGKATAN SENSITIVITAS SENSOR KOIL DATAR MEMPERGUNAKAN SOFT MAGNETIC VITROVAC - Defrianto; Tengku Emrinaldi; Sultan Fiddunya Fiddunya; Rahmondia N. Setiadi; Lazuardi Umar (JOURNAL ONLINE OF PHYSICS, 2019)
This study reports the design of non-magnetic plate thickness sensors based on Eddy Current principld in the form of flat coils. The principle used in the Eddy Current sensor is a change of mutual coil inductance due to the presence of objects in the magnetic field. The coil is made up of single and double layer coil designed using Corel Draw Software based on printed circuit board (PCB) material with dimensions of 152.4 mm x 101.6 mm, which has a track distance of 0.125 m. Single and double layer coil inductance evaluations are carried out using the EVB LDC 1000 L/V Converter module which converts plate thickness into inductance values. The addition of a 30 mm Vitrovac thin film mounted in the direction of the winding in the 2 mm diameter coil core has been carried out to increase the sensitivity value of the sensor which gives an increase in sensitivity value of S = 0.321 uH / mm or 33.2%. The coil is able to measure plate thickness up to 10mm well.